A organização da vegetação arbórea na paisagem urbana de Cachoeira do Sul-RS - Lindenmaier, Diogo de Souza (2013)
The city seen as a landscape has in the green element a key component in the organization of space. For its functionalities presented, the trees are an essential element to improving environmental quality and subsequent quality of life. This study aimed to understand the processes and elements involved structural and spatial organization of trees in the urban landscape of Cachoeira do Sul-RS/Brazil, characterizing the interactions that operate in different process space occupation by the trees along the historical process. The trees were classified according to the space it occupies in: afforestation roads, green areas, urban forests and vegetation in yards and gardens. All these spaces were evaluated and characterized its richness, tree diversity, beyond the phytogeographic origin of species and individuals. Still, was examined through analysis of tree cover the amount of space in square meters occupied by afforestation and its setting in the landscape. Another important test for understanding the organization's current afforestation was evaluating social actions by the government and private sectors, as well as social actors who influenced the policies of afforestation over time historic site. From this evaluation can be considered that the Cachoeira do Sul presents significant forestation in quantitative terms, such as high species richness, diversity and green area index and coverage. However, qualitatively the urban green presents problems. lack of space, floristic homogeneity, excessive pruning, presence of plant parasites, aging vegetation, lack of maintenance, and lack of planning and new projects.